دور مواقع التواصل الإجتماعي في ظاهرة الطلاق - أنور اسماعيل السريح تهاني; عبدالله مغامس منتظر (Journal of College of Education, 2021)
Over the ages,societies have witnessed a wide change at the material and cultural levels due to development . Industrial, technical and scientific progress, until development has reached its peak in our time in all fields, and the field of technical communications and social communication via the Internet has had the best luck until it has become one of the necessities of social life as a result of the many services it provides in various fields . Reliance on Internet services has increased due to the ease of use and its speed, in addition to the approximation of distances, the abolition of the place element and the transfer of cultures between societies, but on the other hand, it has limited real social interaction and receded social relations in the virtual community through social media, all of which would create new social problems as a result of excessive and bad use of the Internet. Social networking sites have produced several risks that affected the social construction of the family and marital relations in particular and contributed to fueling marital problems and disputes until they contributed to the exacerbation of the phenomenon of divorce due to the outlets offered by social networking sites being a fertile ground for the growth of new social relationships and facilitating communication with others in the easiest ways and in all time. Hance, the research sheds light on the most important problem that the family may be exposed to, which is the problem of divorce and the consequent obstacles to the spouses, children and society as a whole. To this phenomenon from a new angle based on the impact of social life on the consequences of technical progress that affected all fields of life, social relations and their nature were affected after the technical development added its touches on social media and thus constitutes a danger to the permanence of a happy family life, and the phenomenon of divorce has exacerbated due to the excessive and bad use of social media.